What do men and women envy each other for? - Kimplova, Tereza; Krakovska, Michaela; Badosek, Radim; Cakirpaloglu, Panajotis (Frontiers in Psychology, 2024)
The present study examines the phenomenon of envy directed towards the opposite sex. The research was conducted in the Czech Republic using a demographically representative sample of 1,769 individuals (867 men and 902 women). A qualitative analysis was conducted on the responses of respondents to the question of what they envied about the opposite sex. A total of 32 categories were identified, with some exhibiting a notable discrepancy between the responses of men and women. These findings corroborate the existing evidence of a sex imbalance. To illustrate, women expressed envy towards men in relation to their salary, prestige, lack of concern, ability to urinate standing up, physical strength, and the absence of menstruation, childbirth, and menopause. This suggests that women envy men in domains that are linked to the female biological condition. Conversely, men expressed envy towards women in relation to their physical attractiveness, ease of seduction, ability to perform "women's work", breasts, motherhood, and the capacity to manage multiple tasks simultaneously. Some categories (safety, tolerance) exhibited a near-equal representation of men and women, yet their content differed markedly.For instance, women envied men for not having to be afraid to be alone, while men envied women for being protected by men. The study revealed a previously unidentified phenomenon: the envy of the absence of an unpleasant quality, which we designated as ablative envy.